Chachapoya Toponymy. A work of linguistic recovery - Valqui Culqui, Jairo (2004)
The toponymic investigations carried out with the objective of recovering features of extinct languages in our country have generally been based on lists of toponyms collected either orally in the places of the geographical area of the supposed language found or in written form from local maps, bibliographic sources or from the National Charts of the National Geographic Institute of Peru.